Sistem Smart Monitoring pada Budidaya Tomat Cherry di Media Tanah - Duma Kristina Yanti; Karel Octavianus; Lanny W; Zefanya, Maria; Sereati, Catherine Olivia (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Living a healthy lifestyle is one of the important aspects for human well-being. One way to start a healthy lifestyle is by consuming fruits and vegetables. Cherry tomatoes have become a popular alternative for a healthy snack. The quality of healthy fruits is, of course, supported by healthy plant growth. Therefore, a smart monitoring system for cherry tomato plant growth was developed to assist cherry tomato farmers in monitoring the quality of plant growth. This system is designed using two systems: image processing using the Orange application to assess the fertility quality of plants, with data captured through a camera. The second system is an environmental monitoring system for plant growth, obtained through LDR, thermistor, and soil moisture sensors. The sensor data is processed using a Multiplexer and WeMos as the controller, and the results are displayed on the Thingspeak website. The designed system indicates the health quality experienced by the test plants, and users can view the sensor readings on the web to observe various environmental factors influencing the plants. Based on the results of several experiments, it is known that the system can function according to the initial goals, and environmental factors affect the quality of plant growth, although they may not be the primary factors.